Equity research | Netflix Inc. (Nflx) - Netflix´s gambit of original content - Rodrigues, Ana Isa Vicente (2021)
The present report serves to expose the current and future Netflix’s state, plus the market and competition analysis. Additionally, there is a special focus placed on 2020 year, due to the global pandemic circumstances, where the impact it is included on valuation. Subsequently, considering the implicit risks ,it was possible to reach a target share price of $605bythe end of2021.Nevertheless, some sensitivity analyses were carried out in order to recognize the share price variation according to certain assumptions.